Implikasi Yuridis Perluasan Objek Notifikasi Pengambilalihan Aset Berdasarkan PerKPPU Nomor 3 Tahun 2023 terhadap Kepastian Hukum Pelaku Usaha - Pinkan Angeline (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
PerKPPU No. 3 of 2023 expanded the scope of asset acquisition notification, and this article examines what that expansion means for legal certainty, particularly whether it opens the door to ultra vires action. Using a normative legal method built on legislative and conceptual approaches, the analysis finds the regulation substantively sound, bringing merger control oversight in line with how business transactions actually work today. The hierarchical picture is less comfortable. Because the notification requirement reaches beyond what the higher-ranking regulations explicitly authorize, the expansion sits on shaky validity grounds when read through Hans Kelsen’s Stufenbau theory, and it exposes a tension between legal certainty and utility along the lines Gustav Radbruch described. The European Union and Singapore offer a useful contrast, since both jurisdictions already treat asset acquisitions as reviewable wherever they produce a change in control or shift market structure. The expansion in Indonesia is therefore justified in substance, but it still needs a firmer legal foundation before it can operate without generating uncertainty for business entities.